СИНОНІМІЧНІ ЗВ’ЯЗКИ У ТЕРМІНОЛЕКСИЦІ КРИМІНАЛЬНО-ПРОЦЕСУАЛЬНОГО ПРАВА (Zaporizhzhia Historical Review, 2021)
The article analyzes the synonyms in the terminology of the law of crimes and procedures on the bases of the Code currently in force; the peculiarities and the types of such links are revealed.